2017
DOI: 10.18203/issn.2454-5929.ijohns20171179
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between microscopic and endoscopic stapes surgery

Abstract: <p class="abstract"><strong>Background:</strong> To investigate whether endoscopic stapes surgery is safer and less invasive than conventional stapes surgery using an operating microscope.</p><p class="abstract"><strong>Methods:</strong> The subjects were 60 patients who were divided consecutively into group A undergoing microscopic stapedotomy and group B undergoing endoscopic stapedotomy. The procedures for endoscopic surgery were fundamentally the same as those for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 10 publications
0
17
0
5
Order By: Relevance
“…Similar results were found by Hunter and Rivas and Harikumar and Arun Kumar. 15,16 In both the groups, the air-bone gap was closed to <10 dB postoperatively and no significant differences were found in this respect. Similarly, the subjective complaints of dizziness or vertigo as reported postoperatively at the end of the first week were same in both groups.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Similar results were found by Hunter and Rivas and Harikumar and Arun Kumar. 15,16 In both the groups, the air-bone gap was closed to <10 dB postoperatively and no significant differences were found in this respect. Similarly, the subjective complaints of dizziness or vertigo as reported postoperatively at the end of the first week were same in both groups.…”
Section: Discussionmentioning
confidence: 87%
“…In contrary to other studies, in our study, the surgical time taken was longer in microscopic stapedotomy than when performed with endoscopes. 7,14,15 This could possibly be attributed to greater time spent to curette/drill the posterior bony wall and more chorda maneuvering to obtain a clear field of view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGPS: A categorical pain rating system consisting of “almost no pain,”“mild pain not requiring analgesia,” or “moderate pain requiring analgesic treatment.” Five studies (35.7%) used this scale. 11-15…”
Section: Resultsmentioning
confidence: 99%
“…11,[13][14][15]17 Eighty percent of studies demonstrated operative time to be shorter or no different in EES. 11,14,15,17 Only 1 study showed a shorter operative time in the MES group but noted that this resolves with mastering of the steep learning curve associated with EES. 13 Transient dysgeusia was significantly lower in the EES group in 2 studies.…”
Section: Qualitative Outcomes By Surgery Typementioning
confidence: 99%